Analisis Pengaruh Tingkat Upah, Modal, Pendapatan dan Jumlah Unit Usaha Terhadap Permintaan Tenaga Kerja Pada Usaha Kecil Menengah Bengkel Motor di Wilayah Surabaya Selatan - Nurdianto, M. Abyan; Sukarsono, Bambang (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2019)
As time goes by the increase in motorized vehicles, especially two wheels in the city of Surabaya, the volume increases, the growth of facilities for the maintenance of motorized vehicles such as motorbikes should be balanced with the number of motorized vehicles in circulation. Small and medium enterprises (UKM) motorbike workshops have a positive influence to continue to be developed to empower the surrounding community and provide employment so that it can help reduce the unemployment rate with the demand for labor. One way to increase the demand for labor, among others, is to streamline wage rates, capital, income and the number of business units. So after the author conducted the study, get the results of the study as follows. Wages and the number of business units do not affect the level of demand for labor in small and medium-sized motorbike workshops in the area of south Surabaya. Then Capital and Revenue affect the level of demand for labor in small and medium sized businesses, motorcycle workshops in the area of South Surabaya.